2020
DOI: 10.1111/cobi.13623
|View full text |Cite
|
Sign up to set email alerts
|

Systematic map of conservation psychology

Abstract: Conservation science and practice commonly draw on the theories and methods of social psychology to explain human cognition, emotion, and behavior germane to biodiversity conservation. We created a systematic map of the cross-disciplinary conservation science literature, which draws on social psychology concepts and methods in their application broadly described as conservation psychology. Established protocols were used to systematically collect and collate peer-reviewed research published in an explicit sele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…We found this focus to be logical, since a focus on residents in an area with prevalent raptor persecution is important to understanding that persecution, and agriculture is the most common threat identified for global raptor populations [ 35 , 36 ]. However, we note an overfocus on general and broadly defined behavioral or sociocultural concepts such as attitudes and values—which is also a trend among general human dimensions of conservation research [ 37 ]—as opposed to other concepts that may be closer antecedents to behavior, such as experience, intentions, mortality, risk perception, and emotions. As the human dimensions of raptor conservation grow and presumably increase its focus on human–raptor interactions, we would urge researchers and practitioners to consider the spectrum of internal and external influences on human behavior [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found this focus to be logical, since a focus on residents in an area with prevalent raptor persecution is important to understanding that persecution, and agriculture is the most common threat identified for global raptor populations [ 35 , 36 ]. However, we note an overfocus on general and broadly defined behavioral or sociocultural concepts such as attitudes and values—which is also a trend among general human dimensions of conservation research [ 37 ]—as opposed to other concepts that may be closer antecedents to behavior, such as experience, intentions, mortality, risk perception, and emotions. As the human dimensions of raptor conservation grow and presumably increase its focus on human–raptor interactions, we would urge researchers and practitioners to consider the spectrum of internal and external influences on human behavior [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus of the present article is not on the exclusive discussion of the determinants of PEA and PEB, a detailed discussion on influential factors can be independently assessed (e.g., Bamberg & Möser, 2007;Gifford, 2011;Hines, Hungerford, & Tomera, 1987;Zmami & Ben-Salha, 2020). This said, understanding human-induced actions with which environmental deteriorations are determined is of useful consideration because "individuals and societies cause and bear the consequences of conservation challenges and are fundamental to solutions" (Wallen & Landon, 2020, p. 1340.…”
Section: / 21mentioning
confidence: 99%
“…A review (Davis et al, 2015) of 276 theory‐based articles on behavioural change found only 6% of the articles focused on populations outside of WEIRD regions (Western, Educated, Industrialized, Rich and Democratic (Henrich, Heine & Norenzayan, 2010)) and only 4% related to environmental conservation (of which none were outside of WEIRD regions). Conducting conservation psychology research in only WEIRD populations not only leads to biased results (Rad, Martingano & Ginges, 2018; Wallen & Landon, 2020), but may also fail to inform conservation within some biodiversity hotspots (Myers et al, 2000; Roberts et al, 2002) and regions with fewer social safety‐nets, where there may be greater conflicts between conservation and livelihoods (Brockington, 2004; Brockington & Wilkie, 2015). The few theory‐driven conservation studies outside WEIRD regions are on the psychological impacts of payment programmes (Rode, Gomez‐Baggethun & Krause, 2015; Akers & Yasué, 2019; Chervier, Le Velly & Ezzine‐de‐Blas, 2019), rather than the much broader suite of community‐based conservation interventions such as education, alternative livelihoods or marine protected areas (MPAs).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have used theories in motivational psychology and behavioural change to better understand environmental conservation (Davis et al, 2015; Cetas & Yasué, 2016). Furthermore, whilst there is a growing body of research on psychological change within people engaging in conservation, much of this research has been conducted in Europe, North America and Australia (Gooden & Grenyer, 2019; Selinske et al, 2019; Wallen & Landon, 2020). A review (Davis et al, 2015) of 276 theory‐based articles on behavioural change found only 6% of the articles focused on populations outside of WEIRD regions (Western, Educated, Industrialized, Rich and Democratic (Henrich, Heine & Norenzayan, 2010)) and only 4% related to environmental conservation (of which none were outside of WEIRD regions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation